Blockade of human HERG K+ channels by rosiglitazone, an antidiabetic drug - Lee, Seung Ho; Sung, Min Ji; Hahn, Sang June; Kim, Jimok; Min, Gyesik; Jo, Su-Hyun; Choe, Han; Choi, Bok Hee (Archives of pharmacal research, 2012)
This study examined the effect of rosiglitazone, an oral antidiabetic drug, on human ether-a-gogo-related gene (HERG) channels expressed in human embryonic kidney (HEK293) cells. Using the whole-cell patch-clamp technique, interaction between rosiglitazone and HERG in HEK293 cells was studied. Rosiglitazone inhibited HERG channels in a concentration-dependent manner, with an IC 50 value of 18.8 μM and a Hill coefficient of 1.0. These effects were reversible after wash-out of the drug. The rosiglitazone-induced inhibition of HERG channels was voltagedependent, with a steep increase in inhibition over the voltage range of channel opening. However, inhibition was voltage-independent over the voltage range in which channels are fully activated. Rosiglitazone did not change the steady-state activation or inactivation curves or the activation or deactivation kinetics, implying that rosiglitazone blocks HERG channels predominantly in the open and inactivated state rather than in the closed state. The present study suggests that rosiglitazone blocks HERG channels by binding to activated and inactivated channels, and rosiglitazone use should thus be carefully monitored in patients with pre-existing QT prolongation.